Diagnosis and management of laryngeal fracture: a case report - Attifi, Hicham; Elfarouki, Ayman; Nadour, Karim; Hmidi, Mounir; Touihem, Nabil; Elboukhari, Ali; Zainoun, Brahim (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Laryngeal fracture is a rare and potentially fatal traumatic injury. Because of the rarity of this type of injury, many laryngeal fractures are often undiagnosed or poorly managed, leading to significant problems with airway patency, voice production, and swallowing. We report a case of a 49 year old man admitted to the emergency room after a motor cycle accident with cervical trauma. The patient presented with hoarseness, anterior neck pain, cervical subcutaneous emphysema, and increasing respiratory distress that led to the tracheostomy of the patient. The computed tomography (CT) of the neck revealed a comminuted fracture of the thyroid cartilage, a hematoma of the left piriform sinus and cervical subcutaneous emphysema. The three-dimensional CT showed a double fracture of thyroid cartilage with displaced intermediate fragment. The patient underwent an open reduction and internal fixation of the thyroid cartilage with miniplates along with laryngeal stenting. He has no significant swallowing or breathing problem and reasonably good voice 6 months after surgery. We conclude that early diagnosis and appropriate therapy favorably alters the prognosis in terms of long-term voice and airway outcome.